2018
DOI: 10.7554/elife.33478
|View full text |Cite|
|
Sign up to set email alerts
|

A randomised double blind placebo controlled phase 2 trial of adjunctive aspirin for tuberculous meningitis in HIV-uninfected adults

Abstract: Adjunctive dexamethasone reduces mortality from tuberculous meningitis (TBM) but not disability, which is associated with brain infarction. We hypothesised that aspirin prevents TBM-related brain infarction through its anti-thrombotic, anti-inflammatory, and pro-resolution properties. We conducted a randomised controlled trial in HIV-uninfected adults with TBM of daily aspirin 81 mg or 1000 mg, or placebo, added to the first 60 days of anti-tuberculosis drugs and dexamethasone (NCT02237365). The primary safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 30 publications
1
95
0
2
Order By: Relevance
“…In order to determine whether there was a relationship between CSF lipid mediator concentrations and disease severity in TBM, we investigated baseline lipid mediator profiles of patients recruited to the aspirin TBM study (NCT02237365) (14). Here, CSF was collected from enrolled patients with known or suspected TBM just prior to the start of treatment in a randomized comparison of aspirin vs. placebo as an adjunct to dexamethasone administration for the first 60 d of TBM treatment (14). Disease severity was assessed using the MRC grade (22), which uses Glasgow coma score and focal neurologic deficits to categorize disease severity as mild (grade 1), moderate (grade 2), or severe (grade 3).…”
Section: Increased Disease Severity Is Associated With a Reduction Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine whether there was a relationship between CSF lipid mediator concentrations and disease severity in TBM, we investigated baseline lipid mediator profiles of patients recruited to the aspirin TBM study (NCT02237365) (14). Here, CSF was collected from enrolled patients with known or suspected TBM just prior to the start of treatment in a randomized comparison of aspirin vs. placebo as an adjunct to dexamethasone administration for the first 60 d of TBM treatment (14). Disease severity was assessed using the MRC grade (22), which uses Glasgow coma score and focal neurologic deficits to categorize disease severity as mild (grade 1), moderate (grade 2), or severe (grade 3).…”
Section: Increased Disease Severity Is Associated With a Reduction Inmentioning
confidence: 99%
“…We recently reported that treatment with aspirin, dexamethasone, and antituberculosis drugs was associated with reduction in new brain infarcts and deaths within 60 d in patients with microbiologically confirmed TBM (14). Therefore, we investigated the impact of aspirin cotreatment with dexamethasone and antituberculosis drugs on CSF lipid mediator pathways in this patient subpopulation (see Supplemental Table S7 for demographics and baseline characteristics).…”
Section: Aspirin Administration Up-regulates Csf Concentrations Of Sementioning
confidence: 99%
“…In order to determine whether there was a relationship between CSF lipid mediator concentrations and disease severity in TBM we investigated lipid mediator profiles of patients recruited to the Aspirin TBM study (NCT02237365). Here CSF was collected from enrolled patients with known or suspected TBM just prior to the start of treatment in a randomised comparison of aspirin versus placebo as an adjunct to dexamethasone administration for the first 60 days of TBM treatment (14). Disease severity was assessed using the Medical Research Council grade (15) that uses Glasgow coma score and focal neurological deficits to categorise disease severity as mild (grade 1), moderate (grade 2), or severe (grade 3; See Supplemental Table 1 for patient information).…”
Section: Resultsmentioning
confidence: 99%
“…We recently tested the hypothesis that the addition of aspirin to standard TBM treatment (anti-tuberculosis drugs and corticosteroids) may further improve outcomes by inhibiting thromboxane A 2 (TxA 2 ) and preventing brain infarcts (a common life-threatening complication of TBM), and by enhancing the resolution of intra-cerebral inflammation through the increased expression of SPMs (14). The trial found that in patients with microbiologically confirmed TBM, aspirin was associated with reduced brain infarcts and/or death in the first 60 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…PGE2 is also known to inhibit anti-bacterial effector functions of phagocytes including phagocytosis, NO production, lysosomal killing and antigen presentation 69 . Incidentally aspirin is currently in clinical trial as adjunct therapy against tuberculosis meningitis in adults 71 . COX2 inhibitors specially non-steroid anti-inflammatory drugs (NSAIDs) like aspirin, ibuprofen, rofecoxib, celecoxib etc.…”
Section: Discussionmentioning
confidence: 99%